Techniques in Minimally Invasive Rectal Surgery (Springer International Publishing, 2018)
This title encompass all current minimally invasive rectal procedures for a variety of benign and malignant indications and provides a compendium of the available data supporting each technique. Procedures are represented both photographically as well as through selected video clips. The video clips are hosted online and provide a valuable addition to the utility of the text. The text has a substantial pathologic emphasis delineating the conditions for which each technique is most suited. It includes established procedures such as laparoscopic proctectomy, but also describes novel approaches that are gaining the attention of professionals throughout the world, such as transanal endoscopic approaches that are being viewed as a bridge toward the natural orifice surgical interventions of the future. The first and only volume dedicated exclusively to advanced minimally invasive rectal surgery and will serve as a precious guide for professionals throughout the world.